Nothing more to tell - McManus, Karen M. (Delacorte Press, 2022)
Brynn Gallagher uses her internship at a new true crime show to investigate the unsolved murder of her favorite teacher, uncovering secrets about her school, her teacher, and her ex-best friend in the process.